A watermarking authentication system for medical images - Zeki, Akram M.; A. Manaf, Azizah; M. Foozy, Feresa; S. Mahmod, Shayma'a (2011)
A watermarking authentication system for medical images has been developed by using a robust Intermediate Significant Bit (ISB) technique. The patient’s information has been embedded within the best locations of the medical images in the Region of Non-Interest (RONI) without affecting the quality of the images. The aim of this study is to solve the missing medical document problem and ensure the medical image is issued from the right source.